Microcontroller Laboratory Practices through Project-Based Learning - Metri, Rajanikant A.; Bharath Pulavarthi, V. R. S. V.; Srikanth, I.; Bhattar, C. L. (Journal of Engineering Education Transformations, 2018)
This paper discusses a course in microprocessor and microcontroller system design in electrical engineering education to facilitate the student learning outcomes through hands-on projects, simulations based on low-cost platform. This course aimed to develop design and technical skills along with communication and team management skills. A project-based learning (PBL) approach was taken into consideration. Students were asked to work on a mini design project. The main focus of the course was on laboratory, where they combined learning of microcontroller, control systems and power electronics courses.Students developed the hardware prototypes using 8051 microcontroller and they were introduced open source hardware like arduino and also encouraged to work on such platform which enabled them to undertake a range of design activities. The students with same wave length came together to form groups. The groups were given a time span of a semester to complete their undertaken project task. Evaluation of this course was obtained from students, staff, and an external examiner, and the results show that the PBL achieved its educational objectives.